Pushing the Boundaries of Chemical Protein Synthesis: The Case of Ubiquitin Chains and Polyubiquitinated Peptides and Proteins. Issue 1 (19th October 2015) - Meledin, Roman; Mali, Sachitanand M.; Brik, Ashraf
Abstract: Chemical synthesis offers unique opportunities to prepare proteins with precise control of the atomic composition. Thanks to recent breakthroughs in synthetic methods, the preparation of large and complex proteins composed of 200–300 residues has now become possible. With these advances, a unique toolbox has been created to enable chemical biologists to investigate proteins that are difficult or even impossible to achieve otherwise, such as posttranslationally modified proteins and proteins composed ofd ‐amino acids. In this review we describe the latest achievements in constructing protein conjugates of record sizes, such as those that are involved in the ubiquitin system. Abstract : Chemical protein synthesis enables precise control over the atomic composition and allows the generation of analogues that are otherwise difficult to achieve. In the current review, we describe recent achievements in the synthesis of large and complex proteins, paving the way for a variety of biochemical and biophysical studies.